„Podłe życie miałem”. "Puszczyk" Stefana Grabińskiego wobec modernistycznego dekadentyzmu - Lesińska, Aleksandra (Załącznik Kulturoznawczy, 2023)
“I Had a Rough Life:” Stefan Grabiński’s Puszczyk and the Decadent Movement in Modernism The article is an attempt to analyze Puszczyk [Tawny Owl], Stefan Grabiński’s first fantastic horror novella, thus introducing this little-known work into the study of pessimistic attitudes prevailing during Modernism, i.e. at the turn of the 19th and 20th centuries. The research is placed in the context of selected approaches to decadence as one of the leading philosophical movements of the era and one which perfectly reflected the mood and melancholic attitudes of the time when the literary work was created. The novella is shown to have the most characteristic features of decadence and corresponds with the general atmosphere and poetics of Polish modernism. Decadence is understood here as an “attitude towards culture, society, civilization, and a certain way of thinking about them” that focuses on “fall, disintegration, or decline.”